The Effect of the Agriculture Sector on Poverty in Aceh Province - Ridho Fatwa; Srinita Srinita; Muhammad Abrar (Research Collaboration Community (RCC), 2022)
This study aims to analyze the influence of the agricultural sector on poverty in Aceh Province. In this study, the variables used in influencing the poverty level in Aceh Province are the share of Gross domestic product (GDP) in the agricultural sector, labor in the agricultural sector, agricultural land, Farmer Education and Gross Regional Domestic Product (GRDP) per capita. The regression model used in this study is the method of multiple linear regression analysis (ordinary least squares regression analysis) using panel data and a fixed effect approach (fixed effect model) to determine the effect between variables. The results of this study are based on a simultaneous test (Test F) which shows that overall, the independent variables (share of GDP in the agricultural sector, labor in the agricultural sector, agricultural land, Farmer Education and GRDP per capita together show their effect on the poverty level. The results of the study based on a partial test (t test) showed that the share of the agricultural sector GRDP and the GDP per capita variable had a negative and significant effect on poverty and agricultural sector labor had a positive and significant effect on poverty, while the variables of agricultural land and farmer education negative effect, but not significant. The value of Adjusted R-squared in this study is 0.868629. This shows that the 86.86 percent change in the dependent variable, namely the Poverty of Aceh Province, can be explained by the independent variable, namely Share of Agricultural GRDP, Agricultural Manpower, Agricultural Land, Farmer Education and Per Capita GRDP. While the remaining 13.14% is explained by other factors outside the model.